Oral history en het vreemde sterven van het Nederlandse christendom - Rooden, P. van (BMGN - Low Countries Historical Review, 2004)
Oral history and the strange demise of Dutch Christianity During the last forty years, Dutch society has gone through a sudden and far-reaching dechristianisation process. Sociologists specialising in religion have monitored this development and explained it using the secularist theory. However, an exploratory oral history approach, based on 43 interviews, and using the modern social history of West European religion, propels us in another direction. The vibrant Dutch Christianity of the 1950s was based on collective rituals and discursive practices that were taken for granted. Although it was possible for individuals to become well-versed in this religion, they did not use the religious rites and rituals in order to think about their own situation. This peculiar nature of Dutch Christianity made it very vulnerable to the cultural revolution of the 1960s, interpreted here as the rise within mass-culture of the practices and ideals of the expressive and reflexive self. People did not choose to leave the churches, but instead drifted away, almost without realising it, as the religious practices from their youth gradually became less important within their lives. The churches were unable to create a form of Christianity that could adapt itself to the new ideal and practices of the self and effectively compete in the cultural marketplace. This article is part of the special issue ’Godsdienst in Nederland’.